(untitled) (Eurasian Journal of Learning and Academic Teaching, 2026)
Notarial translation represents a specialized field of translation practice that requires high linguistic precision and deep knowledge of legal terminology. The accurate translation of official documents such as birth certificates, marriage certificates, academic diplomas, and legal contracts is essential for maintaining their legal validity in international contexts. This study examines the linguistic and terminological problems encountered in the notarial translation of legal documents between English and Uzbek. Particular attention is given to lexical equivalence, structural differences between the two languages, and cultural or institutional discrepancies reflected in legal terminology. Drawing upon translation theory and comparative linguistics, the research analyzes strategies such as borrowing, calque, functional equivalence, and structural adaptation. The findings demonstrate that successful notarial translation depends not only on linguistic competence but also on the translator’s familiarity with legal systems and document conventions. The study contributes to translation studies by highlighting practical strategies that ensure accuracy, clarity, and legal reliability in bilingual documentation.